Association between human leukocyte antigen alleles and COVID-19 disease severity - Ali Hajeer; Dunia Jawdat; Salam Massadeh; Nora Aljawini; Malak S. Abedalthagafi; Yaseen M. Arabi; Manal Alaamery (Elsevier, 2024)
Background: the human leukocyte antigen (HLA) loci have been widely characterized to be associated with viral infectious diseases. Several studies including various ethnic groups and populations suggested associations between certain HLA alleles and SARS-CoV-2 infection. Despite the numerous associations identified, the role of HLA polymorphisms in determining the individual response to SARS-CoV-2 infection is controversial among different Saudi populations. Method: Here, we performed HLA typing by next-generation sequencing to investigate if variations in polymorphic HLA genes are linked to COVID-19 severity in the Saudi population. Namely, we analyzed HLA loci at allele level in 575 Saudi patients with SARS-CoV-2 infection. HLA class I and class II frequencies in patients were compared with allele frequency data from healthy Saudi population. Results: in our cohort HLA-A* 02:01:01 G was associated with mild disease but was not associated with moderate and severe disease. HLA-B* 51:01:01 G was protective from severe disease while HLA-B* 50:01:01 G, HLA-C* 06:02:01 G and HLA-DRB1 * 07:01:01 G were associated with risk to severe disease as well as the total COVID-19 cohort. HLA-DRB1 * 15:01:01 G was associated with risk to all severity groups. Conclusion: in conclusion, we found significant associations between HLA alleles and COVID-19 disease severity in Saudis. Further studies are warranted to include HLA typing in the workup for any new COVID-19 patients.